Efficient slepian-wolf based proof of retrievability using splitting and partitioning scheme for cloud storage - Tan, Choon Beng (2018)
Cloud storage is an online storage service offered by Cloud Service Provider (CSP), where client’s data is hosted on cloud servers’ side. However, as client does not have physical access to outsourced data, cloud storage sometime labelled as untrustworthy or semi-trustworthy. To ensure cloud data integrity and availability, which are the precondition for the existence of a cloud storage system, a protocol known as Proof of Retrievability (PoR) is introduced. PoR allows cloud storage to proof to the client that the stored data is intact and fully retrievable. Recently, Slepian-Wolf Based Proof of Retrievability (SW-PoR) was introduced to provide cost-efficient and time consistent exact repair mechanism for erroneous outsourced data. However, to achieve maximum resiliency for data correctness, encoding process of SW-PoR requires considerably long computational time compared to the conventional storage method involving replication. Hence, this research proposed two viable solutions as extension to SW-PoR to address this limitation. The solutions are named as Partial Binary Encoding for SW-PoR (PBE-SW-PoR) and Optimized SW-PoR (Opti-SW-PoR). PBE-SW-PoR allows part of the data, A, to be encoded by SW-PoR while the other part of the data, B, is secured by adapting Cyclic Redundancy Check (CRC) and replication. Opti-SW-PoR adapted the concept of partitioning to reduce computation time of SW-PoR. Simulation was conducted to evaluate the performance of the proposed solutions by means of comparison to the original SW-PoR scheme in term of computation time. In the simulation, PBE-SW-PoR and Opti-SW-PoR showed significant reduction with respect to total computation time compared to the original SW-PoR. At data size of 1,000 file blocks, original SW-PoR recorded 835,205.4 seconds of total computation time. In comparison to original SW-PoR, PBE-SW-PoR shorten the total computation time by 89.72% while Opti-SW-PoR shorten the total computation time by 99.99%.